2016
DOI: 10.1016/j.mam.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological targeting of the HIF hydroxylases – A new field in medicine development

Abstract: In human cells oxygen levels are 'sensed' by a set of ferrous iron and 2-oxoglutarate dependent dioxygenases. These enzymes regulate a broad range of cellular and systemic responses to hypoxia by catalysing the post-translational hydroxylation of specific residues in the alpha subunits of hypoxia inducible factor (HIF) transcriptional complexes. The HIF hydroxylases are now the subject of pharmaceutical targeting by small molecule inhibitors that aim to activate or augment the endogenous HIF transcriptional re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
131
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(132 citation statements)
references
References 206 publications
(309 reference statements)
0
131
0
1
Order By: Relevance
“…Structures of the P317R, R371H and R396T variants with a clinically used inhibitor628 reveal similar overall folds to wt PHD2, that is, a modified double-stranded-β-helix (DSBH) core (β-strands I–VIII), supporting 2OG and His-X-Asp…His-mediated Fe(II) binding. The structures suggested that these variants probably manifest altered substrate binding (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Structures of the P317R, R371H and R396T variants with a clinically used inhibitor628 reveal similar overall folds to wt PHD2, that is, a modified double-stranded-β-helix (DSBH) core (β-strands I–VIII), supporting 2OG and His-X-Asp…His-mediated Fe(II) binding. The structures suggested that these variants probably manifest altered substrate binding (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…As HIF target genes include those encoding for erythropoietin, vascular endothelial growth factor and many medicinally important proteins, therapeutic manipulation of the HIF system, in particular by PHD inhibition, is of interest. PHD inhibitors are in clinical trials for anaemia treatment via HIF-mediated erythropoietin upregulation67, although these inhibitors are not PHD isoform selective.…”
mentioning
confidence: 99%
“…Therefore, interfering with the HIF response may be a potential therapeutic approach for the control of immune-related disorders 13,129 . A number of pharmacological options for interference with the HIF pathway exist.…”
Section: Targeting the Hif Pathwaymentioning
confidence: 99%
“…Hydroxylase inhibitors have recently been entered into clinical trials for the promotion of erythropoiesis in models of chronic kidney disease-associated anemia (116)(117)(118). In these studies, the delivery of systemic doses of hydroxylase inhibitors was well tolerated by patients, paving the way for the possible use of these reagents for the treatment of inflammatory disorders and/or infectious disease.…”
Section: Clinical Potential Of Hydroxylase Inhibitorsmentioning
confidence: 99%